A concrete prepreg and high performance concrete prepared therefrom
By using acrylate monomers in the prepreg agent to polymerize on the concrete surface, polymerization is formed, which solves the problems of high water absorption and poor durability of concrete, and significantly improves the durability and mechanical properties of concrete.
Patent Information
- Application Number
- CN202211159282.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-22
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-09-22
AI Technical Summary
The existing concrete materials have high water absorption due to their porous structure, which is prone to diseases such as freeze-thaw resistance, chloride ion erosion and carbonization resistance, affecting their structural durability.
A prepreg agent is used, which consists of acrylate monomers, initiators, catalysts and impermeable agents. By prepreg treatment at room temperature, it penetrates into the concrete surface layer, and then polymerization reaction is initiated by heating, microwave or ultraviolet radiation to form a continuous polymer acrylate polymer to seal the pores and cracks of the concrete.
Effectively reduce the water absorption rate of concrete, improve its anti-freeze-thaw, anti-chlorine ion and carbonization properties, and significantly improve the durability and mechanical properties of concrete.
Smart Images

Figure 220922165309 
Figure 220922165312 
Figure DEST_PATH_IMAGE007
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-performance concrete material preparation, and in particular relates to a concrete prepreg and high-performance concrete prepared with the same. Background Art
[0002] Concrete is an important engineering material with a porous structure. The porous structure leads to high water absorption, which easily causes freeze-thaw resistance, chloride ion corrosion resistance and carbonation resistance, affecting its structural durability. In severe cases, it may lead to engineering safety hazards. Improving the durability of concrete is a systematic project. Starting from the concrete mix ratio and preparation process is a common measure in the new construction period. In recent years, with the increase in concrete structures, surface treatment technology has become an economical, efficient and sustainable method for treating concrete durability.
[0003] Common treatment methods for concrete surface treatment include: (1) Cement-based penetrating crystalline waterproof coating. This type of material is mainly silicate treatment agent. Common products include sodium silicate, calcium silicate, etc. It penetrates into the pores of the surface layer of concrete structure, thereby improving the surface density of concrete material and improving durability. However, although this material improves the density of concrete material, it cannot completely seal the porous structure of concrete material, and the degree of improvement in concrete durability is limited. (2) Silane impregnation material treatment. The main component of silane impregnation material is alkyl alkoxy silane. The alkoxy group in its molecule is easily hydrolyzed into silanol in the alkaline environment of concrete. Silicol can react chemically with active substances on the surface of concrete to form -Si-O-Si- structure. The alkyl group at the other end acts as a hydrophobic group to give concrete good hydrophobicity, forming a hydrophobic layer 3-10mm on the surface of concrete. By reducing the water absorption rate, the freeze-thaw resistance and chloride ion resistance of concrete are improved. Silane materials can effectively block the transmission of water and harmful ions in water, thereby achieving the purpose of improving the durability of concrete. However, silane materials do not treat the porous structure of concrete, so they cannot block the transmission of carbon dioxide. Although the carbonization of concrete caused by carbon dioxide can be effectively alleviated by reducing the amount of water absorbed, the improvement of the anti-carbonization performance of concrete is limited. (3) Concrete surface coating treatment mainly adopts the method of multi-layer polymer compound composition to treat the concrete surface. The most commonly used combination system is epoxy primer, epoxy intermediate paint and polymer topcoat, which forms a dense polymer film on the concrete surface, thereby blocking the corrosion of various harmful components to the concrete and improving the durability of the concrete. However, both epoxy and polyurethane have problems with interface adhesion and adhesion attenuation, so their durability is poor and the recoating performance is also poor. By filling the pores on the surface of concrete, the durability of concrete can also be effectively improved, and the strength of concrete can be improved. However, the physical filling of silica system is mostly used, and the effect is difficult to achieve the expected effect. Summary of the invention
[0004] In view of the problems and shortcomings in the prior art, the object of the present invention is to provide a concrete prepreg and high performance concrete prepared therefrom.
[0005] Based on the above purpose, the present invention adopts the following technical solution:
[0006] The first aspect of the present invention provides a prepreg, which is mainly formed by mixing the following raw materials in parts by weight: 100 parts of acrylate monomers, 0.1-5 parts of initiators, 0.1-5 parts of catalysts and 1-5 parts of penetration aids; the acrylate monomers include methacrylic acrylate monomers and / or acryl-containing acrylate monomers or a combination of the two.
[0007] Preferably, the methacryloyl-containing acrylic ester monomer is one or more of methyl methacrylate, butyl methacrylate, tert-butyl methacrylate, and dodecyl methacrylate; the acryl-containing acrylic ester monomer is one or more of methyl acrylate, butyl acrylate, tert-butyl acrylate, and dodecyl acrylate.
[0008] More preferably, the acrylic ester monomer is a methacryloyl-containing acrylic ester monomer. This is because, on the one hand, the α position of the methacryloyl-containing acrylic ester monomer is a methyl group, while the α position of the acryloyl-containing acrylic ester monomer is a hydrogen group, which has a higher reactivity. Therefore, the methacryloyl-containing acrylic ester monomer is more stable to light and oxygen than the acryloyl-containing acrylic ester monomer, and has better weather resistance, light resistance, and water resistance. On the other hand, the methyl group at the α position has a steric hindrance effect on the free rotation of its main chain, and the movement of the molecular chain is affected. Therefore, the methacryloyl-containing acrylic ester monomer polymer generally exhibits greater rigidity than the acryloyl-containing acrylic ester monomer polymer, and the long-chain acrylic ester monomer polymer will exhibit good flexibility.
[0009] Preferably, the acrylic acid ester monomer is a combination of one or more of butyl methacrylate, tert-butyl methacrylate, dodecyl methacrylate and methyl methacrylate.
[0010] Furthermore, in order to avoid a large amount of volatilization of the acrylic ester monomers, when the acrylic ester monomers include methyl acrylate and / or methyl methacrylate, the mass of the methyl acrylate and / or methyl methacrylate does not exceed 20% of the total mass of the acrylic ester monomers. Preferably, the amount of methyl methacrylate accounts for 5%-20% of the total mass of the acrylic ester monomers.
[0011] Preferably, the penetration aid is a small molecule solvent and / or a silane coupling agent; the silane coupling agent is a vinyl-containing silane coupling agent and / or an amino-containing silane coupling agent; the small molecule solvent is one or more of acetone, ethanol, and propanol; the vinyl-containing silane coupling agent is one or more of vinyltriethoxysilane, vinyltrimethylsilane, and vinyltri(β-methoxyethoxy)silane; the amino-containing silane coupling agent is one or more of aminotriethoxysilane, aminotrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
[0012] Preferably, the initiator is at least one of azobisisobutylcyanide, dibenzoyl peroxide, and dodecanoyl peroxide.
[0013] More preferably, the initiator is dibenzoyl peroxide; the mass ratio of dibenzoyl peroxide to acrylate monomer is 1%-5%.
[0014] Preferably, the catalyst is dimethylaniline and / or cobalt naphthenate.
[0015] The second aspect of the present invention provides the use of the pre-impregnating agent described in the first aspect in high molecular polymer impregnation concrete.
[0016] The third aspect of the present invention provides a method for preparing high molecular polymer impregnated concrete, comprising the following steps:
[0017] (1) applying the prepreg prepared in the first aspect above to the surface of concrete to be impregnated to obtain prepreg concrete;
[0018] (2) The pre-impregnated concrete prepared in step (1) is subjected to heat treatment or irradiation treatment to undergo a polymerization reaction to obtain a high molecular weight polymer impregnated concrete.
[0019] More preferably, the strength grade of the concrete to be impregnated is C30-C60; the concrete to be impregnated can be prepared by the method specified in GB / T 50107.
[0020] Preferably, the coating amount of the pre-impregnant is 300-2000 g / m based on the surface area of the concrete to be impregnated. 2 More preferably, the coating amount of the prepreg is 500-1000g / m 2 .
[0021] Furthermore, the coating amount of the prepreg and the strength grade of the concrete to be impregnated affect the penetration depth of the prepreg. The greater the amount of the prepreg, the lower the strength grade of the concrete to be impregnated, and the greater the penetration depth.
[0022] More preferably, the coating method includes but is not limited to roller coating, brush coating and spray coating; the coating can be carried out by dipping in multiple passes, and the next pass is required to be carried out after the previous pass is fully penetrated.
[0023] More preferably, the concrete to be impregnated is first dried before being coated with the pre-impregnant; the drying condition is 80° C. for 6-12 hours.
[0024] More preferably, the prepreg concrete can be coated with epoxy resin or polyurethane sealing coating with curing agent added on the surface of the prepreg concrete before the polymerization reaction, and then removed after the polymerization reaction. The use of sealing coating can effectively prevent the volatilization of components in the prepreg agent.
[0025] Preferably, the heat treatment condition in step (2) is heating at 80-110° C. for 1-12 h.
[0026] More preferably, the irradiation treatment in step (2) is ultraviolet irradiation or microwave irradiation or a combination of the two.
[0027] More preferably, the pre-impregnating agent is replaced with other polymerizable compositions, and the preparation method described in the third aspect can still be used as a concrete surface treatment technology for preparing high-performance concrete.
[0028] The fourth aspect of the present invention provides high molecular polymer impregnated concrete prepared by the preparation method described in the third aspect.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention utilizes a pre-impregnation-post-polymerization concrete surface treatment method to prepare high-performance concrete. Specifically, an acrylate monomer with polymerization function that maintains a small molecule composition state at room temperature is used as a monomer material of the pre-impregnant. With the help of a penetration enhancer, the acrylate monomer can penetrate into the concrete surface layer 20 mm deep. Then, the concrete impregnated with the pre-impregnant is subjected to heating, microwave or ultraviolet radiation and other technical means to initiate polymerization of the small molecule monomer, so that the pre-impregnated small molecule monomer composition forms a continuous high molecular weight acrylate polymer in the porous structure of the concrete. The high molecular weight polyacrylate forms a continuous structure in the surface voids of the concrete structure with a long chain structure, thereby forming a protective system on the surface of the concrete. This type of polymer is distributed in the porous structure of concrete in the form of long-chain polymers and forms a continuous flexible phase, which can not only seal the surface pores of concrete, reduce the porosity of concrete, and block the erosion of concrete structure by water and harmful substances with water as the medium, effectively improving the durability of concrete; and because the surface of concrete is filled with polymer macromolecules, a continuous reinforcement network in any direction is formed between the three phases of polymer-aggregate-cement paste, which can make the concrete structure denser, so it can significantly improve the strength and toughness of concrete, thereby avoiding the cracking of concrete structure. The prepreg prepared in this application can improve the mechanical properties and durability of concrete, and can be used for the high performance of ordinary concrete structures.
[0031] (2) The present invention preferably uses methyl methacrylate and butyl methacrylate as monomer compositions to prepare prepregs, which combine long and short chains and soft and hard components. After impregnation and polymerization of the base concrete, a high-strength concrete block with flexibility, rigidity and low compression and flexural strength can be obtained. In one embodiment, concrete is treated with a prepreg prepared from methyl methacrylate and butyl methacrylate, which can increase the compressive strength of the concrete from 40MPa to 120MPa, increase the flexural strength from 7.5MPa to more than 20MPa, reduce the water absorption rate by more than 96%, increase the number of freeze-thaw cycles by more than 270 times, reduce the carbonization depth from 15mm to less than 0.5mm, and reduce the chloride ion diffusion coefficient by more than 96%. Therefore, after the prepreg polymerization reaction treatment, the strength and durability of the concrete are greatly improved. At the same time, in the screening of penetration enhancers, the inventors found that aminosilanes have the best penetration-enhancing effect. In one embodiment, when the pre-impregnant with aminotrimethoxysilane as the penetration enhancer is impregnated into concrete, the impregnation depth reaches 35 mm, which is 42% higher than the impregnation depth of the pre-impregnant without the penetration enhancer. In addition, when screening the coating amount of the pre-impregnant, the inventors found that when the pre-impregnant prepared by the present invention is used to impregnate concrete, the coating amount of 800 g / m 2 The coating amount can optimize the comprehensive performance of concrete.
[0032] (3) The present invention preferably uses heat treatment to polymerize the concrete impregnated with the prepreg. This is because in actual production and application, heat sources are easily available, equipment investment is small, and it is easy to use. It is more suitable for thick-walled, irregular-shaped large products, has a fast polymerization speed, and can meet a variety of application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a microscopic morphology of the concrete surface before the pre-impregnation agent of the present invention is impregnated and polymerized;
[0034] Figure 2 This is a microscopic morphology of the concrete surface after impregnation and polymerization treatment with the pre-impregnating agent of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below by means of embodiments in combination with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0036] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0037] It should be noted that the present application adopts the method of directly measuring after destruction under the action of an indicator to determine the immersion depth; the compressive strength and flexural strength of the sample are measured in accordance with the requirements of GB / T 50081; the water absorption of the sample is measured in accordance with the method in "Standard Test Method for Measurement of Rate of Absorption of Water by Hydraulic Cement Concretes" (ASTM C1585-2013), and the treatment time is 24 hours; the freeze-thaw cycle resistance grade, carbonization depth (treatment time 72 hours), and chloride ion diffusion coefficient of the sample are measured in accordance with the provisions of GB / T 50082. Among them, the water absorption reduction rate = (water absorption of the un-immersed blank sample - water absorption of the test example / embodiment / comparative example sample) / water absorption of the un-immersed blank sample, and the chloride ion diffusion coefficient reduction rate = (chlorine ion diffusion coefficient of the un-immersed blank sample - chloride ion diffusion coefficient of the test example / embodiment / comparative example sample) / chloride ion diffusion coefficient of the un-immersed blank sample.
[0038] Example 1: Preparation of prepregs with different monomer types and monomer ratios
[0039] The present embodiment provides a prepreg, which is prepared by uniformly stirring the following raw material components in parts by mass; the raw material components include: 100 parts of acrylate monomers, 5 parts of dibenzoyl peroxide, 0.1 parts of cobalt cyclohexane, and 1.5 parts of vinyl triethoxysilane.
[0040] The types and amounts of the acrylic acid ester monomers are shown in Table 1.
[0041] Table 1 Types and amounts of acrylate monomers used to prepare pre-impregnants
[0042]
[0043] Example 2: Effects of pre-impregnating agents with different monomer types and monomer ratios on the properties of prepared polymer-impregnated concrete
[0044] In order to explore the effect of the pre-impregnant on the impregnation depth, compressive strength, flexural strength, water absorption reduction rate, freeze-thaw cycle resistance grade, carbonation depth, and chloride ion diffusion coefficient reduction rate of the prepared high molecular polymer impregnated concrete, the inventors conducted the following experiments, namely test examples and blank examples, to compare the effects of the pre-impregnation treatment and non-impregnation treatment of the pre-impregnant 1-9 prepared in Example 1 on the performance of concrete. The results are shown in Table 2.
[0045] Test example
[0046] This embodiment provides a high molecular polymer impregnated concrete, and the preparation method thereof comprises the following steps:
[0047] (1) After curing the impregnated concrete specimen with strength grade C30 for 28 days, the specimen was dried at 80°C for 8 hours to obtain a dried concrete specimen;
[0048] (2) The prepreg prepared in Example 1 was applied by brushing at a pressure of 800 g / m 2 The coating amount is evenly applied on the surface of the concrete specimen to be impregnated after drying prepared in step (1) to obtain pre-impregnated concrete;
[0049] (3) To prevent the monomer from volatilizing, the surface of the pre-impregnated concrete is covered with epoxy resin coating. After the epoxy resin coating is cured, the pre-impregnated concrete is heat treated in an oven at 80°C for 12 h to carry out polymerization reaction. After removing the epoxy resin coating, the high molecular weight polymer impregnated concrete is obtained.
[0050] Blank example
[0051] A concrete preparation method comprises the following steps: curing a concrete specimen to be impregnated with a strength grade of C30 for 28 days and then drying it at 80°C for 8 hours to obtain a dried concrete specimen to be impregnated.
[0052] Table 2 The usage of prepreg and concrete performance data in test examples 1 to 9 and blank example
[0053]
[0054] After comparing the test case with the blank case, it was found that the compressive strength of the polymer impregnated concrete (test case) after impregnation treatment was 2.8-3.5 times higher, the flexural strength was 2.6-4.6 times higher, the water absorption rate was reduced by more than 95%, the freeze-thaw cycle resistance level was increased by more than 270 times, the carbonization depth was reduced by more than 98%, and the chloride ion diffusion coefficient was reduced by more than 96%. This is because the monomer composition in the pre-impregnating agent undergoes a polymerization reaction after thermal initiation, which significantly reduces the porosity of the concrete, significantly reduces the number of large-diameter pores, and also closes the microcracks, the continuity between the pores and cracks is cut off, and the interior of the concrete is more compact. At the same time, the hydration product is wrapped by the polymer, which separates it from the external environment, acts as a physical protective layer, and improves the durability of the concrete. Therefore, the use of pre-impregnating agent to impregnate concrete can significantly improve the mechanical properties of concrete and improve the durability of concrete.
[0055] As can be seen from Table 2, by comparing Test Examples 1 to 3, Test Examples 4 to 6 and Test Examples 7 to 9, it can be found that with the increase of methyl methacrylate content, the impregnation depth of the high molecular polymer impregnated concrete after impregnation treatment all shows an increasing trend, the compressive strength all shows a decreasing trend, the flexural strength shows a decreasing trend, and other parameter indicators are not highly correlated with the content of methyl methacrylate. This is because the molecular volume of methyl methacrylate is relatively small, which is conducive to the migration and penetration of the pre-impregnant in concrete, but the melting point of methyl methacrylate is relatively low, and it is easy to volatilize when heated, resulting in less pre-impregnant in which polymerization reaction actually occurs. Therefore, the present application preferably uses a pre-impregnant with a methyl methacrylate content of 5%-20% to impregnate concrete.
[0056] As can be seen from Table 2, by comparing the test examples with the same methyl methacrylate content, such as comparing test examples 1, 4 and 7, it can be found that with the increase of the molecular weight of another acrylic ester monomer, the impregnation depth of the high molecular polymer impregnated concrete after impregnation treatment shows a downward trend, the water absorption reduction rate and the freeze-thaw cycle resistance grade show an increasing trend, the carbonization depth shows a decreasing trend, and the chloride ion diffusion coefficient shows an increasing trend. This is because the comonomers selected in test examples 4-6 and test examples 7-9 are tert-butyl methacrylate and dodecyl methacrylate. These two monomers are not only large in volume, but also due to steric hindrance and hydrophobicity, their diffusion performance in concrete is reduced, resulting in a decrease in their penetration depth. However, the hydrophobic effect of tert-butyl methacrylate and dodecyl methacrylate is significantly better than that of butyl methacrylate. Even if their penetration depth is slightly reduced, the water absorption of the treated concrete is significantly reduced, and the durability index related to water migration also has an increasing trend. In addition, when the other acrylic ester monomer is tert-butyl methacrylate, its compressive and flexural strengths are significantly higher than those of butyl methacrylate and dodecyl methacrylate. This is because the long-chain dodecyl methacrylate exhibits good flexibility, while tert-butyl methacrylate exhibits greater rigidity, so dodecyl methacrylate is weaker than tert-butyl methacrylate in force transmission. Therefore, methyl methacrylate and butyl methacrylate with better comprehensive performance are preferred for preparing high molecular polymer impregnated concrete.
[0057] Example 3: Effects of different types of penetration enhancers on the properties of prepared polymer-impregnated concrete
[0058] In order to explore the influence of different types of penetration enhancers on the impregnation depth of the prepared high molecular polymer impregnated concrete. The inventors conducted the following experiments, namely, Examples 3-1 to 3-9 and Comparative Example 1, and the corresponding types of penetration enhancers added were: acetone, ethanol, propanol, aminotriethoxysilane, aminotrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethylsilane, vinyltri(β-methoxyethoxy)silane, and no penetration enhancer. The results are shown in Table 3.
[0059] Example 3-1
[0060] The present embodiment provides a pre-impregnant, which is prepared by uniformly stirring the following raw material components in parts by mass; the raw material components include: 100g of methyl methacrylate, 900g of butyl methacrylate, 50g of dibenzoyl peroxide, 1g of cobalt cyclohexaneate and 15g of acetone (penetration aid).
[0061] This embodiment also provides a high molecular polymer impregnated concrete, the preparation method of which includes the following steps:
[0062] (1) After curing the impregnated concrete specimen with strength grade C30 for 28 days, the specimen was dried at 80°C for 8 hours to obtain a dried concrete specimen;
[0063] (2) The prepreg prepared in this embodiment is applied by brushing at a pressure of 800 g / m 2 The coating amount is evenly applied on the surface of the concrete specimen to be impregnated after drying prepared in step (1) to obtain pre-impregnated concrete;
[0064] (3) To prevent the monomer from volatilizing, the surface of the pre-impregnated concrete is covered with epoxy resin coating. After the epoxy resin coating is cured, the pre-impregnated concrete is heat treated in an oven at 80°C for 12 h to carry out polymerization reaction. After removing the epoxy resin coating, the high molecular weight polymer impregnated concrete is obtained.
[0065] The concrete specimens before and after the pre-impregnation polymerization treatment were analyzed by scanning electron microscope (SEM). Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the surface of the unimpregnated concrete is mainly CSH gel and Ca(OH)2. At the same time, pores and microcracks can be seen on the surface, and the density is low. This is caused by the hydration and shrinkage of the concrete during the curing period. This makes the force-bearing area of the concrete smaller, and the macroscopic properties exhibit low mechanical strength. When subjected to a large load, the cracks will expand rapidly and cause the specimen to be destroyed. In addition, the stacking of concrete hydration products is loose, the continuity between hydration products is poor, and the interface strength is low, showing obvious brittle failure characteristics. Figure 2 It can be seen that the surface of concrete after polyacrylate impregnation polymerization is relatively smooth, with a local continuous phase, and the destruction of mortar shows plastic failure characteristics, and the mortar has a certain toughness. This is because the polymer fills the pores inside the concrete, strengthens the contact cracks between the aggregate and the cement paste, improves the density of the substrate, and makes the original porous system become a denser whole. When loaded, the effective bearing area of the concrete increases, and the stress concentration effect caused by pores and cracks is reduced. In addition, the polymer does not fill the specimen uniformly, but forms a continuous reinforcement network in any direction. The bonding of the polymer to the substrate is not ordinary mechanical bonding, but the aggregate and cement paste are wrapped in it during the monomer polymerization process, and the polymer-aggregate-cement paste three phases become a whole under a large bonding force. When subjected to external loads, it will absorb part of the strain energy, and the absorption size is related to the characteristics of the polymer itself. The polymer can inhibit the generation and expansion of cracks while reinforcing the cement composite material, and delay the fracture of the specimen.
[0066] Example 3-2
[0067] The content of a pre-impregnation agent is substantially the same as that of Example 3-1, except that acetone is replaced by ethanol to prepare the pre-impregnation agent.
[0068] The content of a high molecular polymer impregnated concrete is basically the same as that of Example 3-1, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0069] Example 3-3
[0070] The content of a prepreg is substantially the same as that of Example 3-1, except that acetone is replaced by propanol to prepare the prepreg.
[0071] The content of a high molecular polymer impregnated concrete is basically the same as that of Example 3-1, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0072] Embodiment 3-4
[0073] The content of a prepreg is substantially the same as that of Example 3-1, except that acetone is replaced by aminotriethoxysilane to prepare the prepreg.
[0074] The content of a high molecular polymer impregnated concrete is basically the same as that of Example 3-1, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0075] Embodiment 3-5
[0076] The content of a prepreg is substantially the same as that of Example 3-1, except that acetone is replaced by aminotrimethoxysilane to prepare the prepreg.
[0077] The content of a high molecular polymer impregnated concrete is basically the same as that of Example 3-1, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0078] Embodiment 3-6
[0079] The content of a prepreg is substantially the same as that of Example 3-1, except that acetone is replaced by N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane to prepare the prepreg.
[0080] The content of a high molecular polymer impregnated concrete is basically the same as that of Example 3-1, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0081] Embodiment 3-7
[0082] The content of a prepreg is substantially the same as that of Example 3-1, except that acetone is replaced by vinyltriethoxysilane to prepare the prepreg.
[0083] The content of a high molecular polymer impregnated concrete is basically the same as that of Example 3-1, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0084] Embodiment 3-8
[0085] The content of a prepreg is substantially the same as that of Example 3-1, except that acetone is replaced by vinyltrimethylsilane to prepare the prepreg.
[0086] The content of a high molecular polymer impregnated concrete is basically the same as that of Example 3-1, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0087] Embodiment 3-9
[0088] The content of a prepreg is substantially the same as that of Example 3-1, except that acetone is replaced by vinyl tri(β-methoxyethoxy) silane to prepare the prepreg.
[0089] The content of a high molecular polymer impregnated concrete is basically the same as that of Example 3-1, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0090] Comparative Example 1
[0091] The content of a pre-impregnant is substantially the same as that of Example 3-1, except that acetone is not added when preparing the pre-impregnant.
[0092] The content of a high molecular polymer impregnated concrete is basically the same as that of Example 3-1, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0093] Table 3 The usage of penetration enhancers and concrete performance data in Examples 3-1 to 3-9 and Comparative Example 1
[0094]
[0095] As can be seen from Table 3, compared with small molecule solvents (acetone, ethanol, propanol), aminosilane penetration enhancers (aminotriethoxysilane, aminotrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane) are more helpful in improving the permeability of concrete. This is because the alkoxy group of the aminosilane penetration enhancer is easy to form a chemical link with the concrete after hydrolysis, and it is not easy to form a local concentration of the comonomer that is too high, so its permeability is better; although the vinyl silane penetration enhancer (vinyltriethoxysilane, vinyltrimethylsilane, vinyltri(β-methoxyethoxy)silane) also has an alkoxy group, due to the hydrophobicity of the vinyl group, its permeability is not as good as that of the aminosilane penetration enhancer. Therefore, the present application preferably uses a pre-impregnating agent prepared with an aminosilane penetration enhancer to impregnate the concrete.
[0096] Example 4: Effect of different penetration enhancer contents on the properties of prepared polymer impregnated concrete
[0097] In order to explore the influence of different penetration enhancer contents on the impregnation depth, compressive strength, flexural strength, water absorption reduction rate, freeze-thaw cycle resistance grade, carbonation depth, and chloride ion diffusion coefficient reduction rate of the prepared high molecular polymer impregnated concrete. The inventors conducted the following experiments, namely, Examples 3-5, Examples 4-1 to 4-5, and Comparative Example 1, and the corresponding mass ratios of the added penetration enhancer to the monomer (methyl methacrylate and butyl methacrylate) were: 1.5%, 1%, 2%, 2.5%, 3%, 5%, and no penetration enhancer. The results are shown in Table 4.
[0098] Example 4-1
[0099] The content of a pre-impregnating agent is substantially the same as that of Example 3-5, except that: the amount of aminotrimethoxysilane added is 10 g; the amount of aminotrimethoxysilane added is 1% of the mass of the monomer.
[0100] The content of a high molecular polymer impregnated concrete is basically the same as that of Examples 3-5, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0101] Example 4-2
[0102] The content of a pre-impregnating agent is substantially the same as that of Example 3-5, except that: the amount of aminotrimethoxysilane added is 20 g; the amount of aminotrimethoxysilane added is 2% of the mass of the monomer.
[0103] The content of a high molecular polymer impregnated concrete is basically the same as that of Examples 3-5, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0104] Example 4-3
[0105] The content of a pre-impregnating agent is substantially the same as that of Example 3-5, except that: the amount of aminotrimethoxysilane added is 25 g; the amount of aminotrimethoxysilane added is 2.5% of the weight of the monomer.
[0106] The content of a high molecular polymer impregnated concrete is basically the same as that of Examples 3-5, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0107] Example 4-4
[0108] The content of a pre-impregnating agent is substantially the same as that of Example 3-5, except that: the amount of aminotrimethoxysilane added is 30 g; the amount of aminotrimethoxysilane added is 3% of the mass of the monomer.
[0109] The content of a high molecular polymer impregnated concrete is basically the same as that of Examples 3-5, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0110] Embodiment 4-5
[0111] The content of a pre-impregnating agent is substantially the same as that of Example 3-5, except that: the amount of aminotrimethoxysilane added is 50 g; the amount of aminotrimethoxysilane added is 5% of the mass of the monomer.
[0112] The content of a high molecular polymer impregnated concrete is basically the same as that of Examples 3-5, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0113] Table 4 The amount of permeation enhancer added and the concrete performance data in the examples and comparative examples
[0114]
[0115] As can be seen from Table 4, with the increase of the content of the penetration enhancer, the impregnation depth, compressive strength and flexural strength of the high molecular polymer impregnated concrete after the impregnation treatment show a trend of increasing first and then stabilizing, and the water absorption reduction rate, freeze-thaw cycle resistance grade, carbonization depth and chloride ion diffusion coefficient all show a stable trend. This is because the penetration enhancer helps to increase the penetration depth of the comonomer, and the compressive and flexural strength of concrete are positively correlated with the impregnation thickness of the sample to be tested, so the addition of the penetration enhancer can increase the impregnation depth and compressive and flexural strength of the pre-impregnant. However, the impregnation depth of the penetration enhancer is limited, so the compressive and flexural strengths of concrete will stabilize after reaching a certain depth. And the water absorption, freeze-thaw cycle resistance and chloride ion migration resistance mainly depend on the surface layer of the concrete (3mm-15mm thickness layer), so the data is relatively stable. Therefore, the present application preferably uses a pre-impregnant with a penetration enhancer aminotrimethoxysilane and a monomer mass ratio of 2.5% to impregnate concrete.
[0116] Example 5: Effect of different pre-impregnant coating amounts on the properties of prepared polymer-impregnated concrete
[0117] In order to explore the effect of different pre-impregnant coating amounts on the impregnation depth, compressive strength, flexural strength, water absorption reduction rate, freeze-thaw cycle resistance level, carbonation depth, and chloride ion diffusion coefficient reduction rate of the prepared high molecular polymer impregnated concrete, the inventors conducted the following experiments, namely, Examples 3-5 and Examples 5-1 to 5-5, and the corresponding pre-impregnant coating amounts added were: 800 g / m 2 , 300g / m 2 , 500g / m 2 , 1000g / m 2 , 1500g / m 2 , 2000g / m 2 The results are shown in Table 5.
[0118] Example 5-1
[0119] The content of a pre-impregnant is substantially the same as that of Example 3-5, except that the coating amount of the pre-impregnant in step (2) is 300 g / m 2 .
[0120] The content of a high molecular polymer impregnated concrete is basically the same as that of Examples 3-5, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0121] Example 5-2
[0122] The content of a pre-impregnant is substantially the same as that of Example 3-5, except that the coating amount of the pre-impregnant in step (2) is 500 g / m 2 .
[0123] The content of a high molecular polymer impregnated concrete is basically the same as that of Examples 3-5, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0124] Example 5-3
[0125] The content of a pre-impregnant is substantially the same as that of Example 3-5, except that the coating amount of the pre-impregnant in step (2) is 1000 g / m 2 .
[0126] The content of a high molecular polymer impregnated concrete is basically the same as that of Examples 3-5, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0127] Example 5-4
[0128] The content of a prepreg is substantially the same as that of Example 3-5, except that the coating amount of the prepreg in step (2) is 1500 g / m 2 .
[0129] The content of a high molecular polymer impregnated concrete is basically the same as that of Examples 3-5, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0130] Example 5-5
[0131] The content of a pre-impregnant is substantially the same as that of Example 3-5, except that the coating amount of the pre-impregnant in step (2) is 2000 g / m 2 .
[0132] The content of a high molecular polymer impregnated concrete is basically the same as that of Examples 3-5, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0133] Table 5 Prepreg coating amount and concrete performance data in Examples 3-5 and Examples 5-1 to 5-5
[0134]
[0135] It can be seen from Table 5 that with the increase in the amount of pre-impregnant coating, the impregnation depth of the high-molecular polymer impregnated concrete after impregnation treatment shows a trend of first rapidly increasing and then tending to be stable, the compressive strength shows a trend of gradually increasing but the increase amplitude gradually decreases, the flexural strength shows a trend of gradually increasing, the water absorption reduction rate and the chloride ion diffusion coefficient show a stable trend, and the freeze-thaw cycle resistance grade and carbonization depth show a slight increase trend. This is because increasing the amount of pre-impregnant can significantly increase the impregnation depth, but due to the large number of factors that hinder diffusion, the impregnation depth does not increase with the increase in the amount of impregnant, and the increase in the impregnation depth is not obvious after reaching a certain level. As the coating amount further increases, the amount of pre-impregnant per unit volume gradually increases, and the filling effect of the polymer on the concrete is further strengthened, so the mechanical properties and durability performance data of the concrete will slightly show a trend of further increase. Therefore, the present application preferably uses 500-1000g / m 2 The concrete is impregnated with a pre-impregnant.
[0136] Example 6: Effects of different polymerization methods on the properties of prepared polymer-impregnated concrete
[0137] In order to explore the effects of different polymerization methods on the compressive strength, flexural strength, water absorption, freeze-thaw cycle resistance, carbonation depth, and chloride ion diffusion coefficient of the prepared high molecular polymer impregnated concrete, the inventors conducted the following experiments, namely, Examples 3-5, Examples 6-1 to 6-2, and the corresponding polymerization methods were: thermal polymerization, ultraviolet polymerization, and microwave polymerization. The results are shown in Table 6.
[0138] Example 6-1
[0139] A pre-preg having the same content as in Example 3-5.
[0140] The content of a polymer impregnated concrete is basically the same as that of Example 3-5, except that: the polymerization reaction conditions in step (3) are ultraviolet polymerization; the ultraviolet polymerization conditions are wavelength 365nm, light intensity 120mW / cm 2 UV light for 2h.
[0141] Example 6-2
[0142] A pre-preg having the same content as in Example 3-5.
[0143] The content of a high molecular polymer impregnated concrete is basically the same as that of Example 3-5, except that: the polymerization reaction condition in step (3) is microwave polymerization: the microwave polymerization condition is 350W, and the microwave irradiation is 1h.
[0144] Table 6 The use of polymerization methods and concrete performance data in Examples 3-5 and Examples 6-1 to 6-2
[0145]
[0146] It can be seen from Table 6 that there is no obvious difference in the compressive strength, flexural strength, water absorption, freeze-thaw cycle resistance grade, carbonization depth, and chloride ion diffusion coefficient of the polymer impregnated concrete after polymerization treatment using different polymerization initiation methods. This is because the polymerization initiation conditions only provide the activation energy required for free radical polymerization. After the polymerization reaction is initiated, the free radical polymerization is basically driven by its own heat. Therefore, this application selects different treatment methods to polymerize the concrete after impregnation treatment according to the conditions of the application site.
[0147] Example 7
[0148] The content of a pre-impregnating agent is substantially the same as that of Example 3-5, except that it contains 50 g of methyl methacrylate and 950 g of butyl methacrylate.
[0149] The content of a high molecular polymer impregnated concrete is the same as that of Example 3-5, except that: in step (2), the pre-impregnating agent prepared in this example is used for impregnation treatment.
[0150] In summary, the present invention effectively overcomes the deficiencies in the prior art and has a high industrial utilization value. The above embodiments serve to illustrate the substantive content of the present invention, but do not limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.
Claims
1. A prepreg, characterized in that: The pre-impregnating agent is prepared by mixing the following raw materials in parts by weight: 100 parts of acrylate monomer, 0.1-5 parts of dibenzoyl peroxide, 0.1-5 parts of cobalt cyclohexaneate and 1-5 parts of a penetration enhancer; the acrylate monomer is a combination of butyl methacrylate and methyl methacrylate; the amount of methyl methacrylate accounts for 10% of the total weight of the acrylate monomer; The penetration enhancer is vinyltrimethylsilane.
2. Use of the prepreg according to claim 1 in high molecular polymer impregnation concrete.
3. A method for preparing high molecular polymer impregnated concrete, comprising the following steps: (1) applying the prepreg according to claim 1 to the surface of concrete to be impregnated to obtain prepreg concrete; (2) The pre-impregnated concrete prepared in step (1) is subjected to heat treatment or irradiation treatment to undergo a polymerization reaction to obtain a high molecular weight polymer impregnated concrete.
4. The preparation method according to claim 3, characterized in that: The coating amount of the prepreg is 300-2000g / m 2 .
5. The preparation method according to claim 4, characterized in that: The heat treatment conditions in step (2) are heating at 80-110° C. for 1-12 hours.
6. The high molecular polymer impregnated concrete prepared by the preparation method according to claim 5.
Citation Information
Patent Citations
Acrylic ester polymer, preparation method and application thereof, acrylic ester polymer coating and application thereof
CN114057935A
Polymer impregnated concrete
GB1143898A
Impregnant compositions for porous substrates
US4556701A
Impregnating agent for concrete
WO2019111768A1